EP840 Hipec at interval debulking surgery in advanced stage ovarian cancer patients: impact of the OVHIPEC-1 trial in real life experience of a tertiary referral centre. (1st November 2019) - Fagotti, A; Ronsini, C; Cianci, S; Costantini, B; Bernardini, F; Corrado, G; Vizzielli, G; Scambia, G
Abstract : Introduction/Background: The OVHIPEC-1 phase III randomized trial has shown a statistically significant improvement in terms of Progression Free and Overall Survival in patients with advanced ovarian cancer, submitted to neoadjuvant chemotherapy (NACT), and receiving HIPEC at time of Interval Debulking Surgery (IDS). Methodology: After the publication of the trial, according to our national guidelines, the GYO Hospital Tumor Board decided to include HIPEC as routine practice, in patients achieving complete/optimal cytoreduction up to 2.5 mm at time of IDS. Procedure was performed according to published methods. Cases were collected prospectively to show rate of accrual, feasibility, complications. Results: From January to April 2019, 40 patients were admitted to our Institution to receive IDS. Among them, 18 (45%) were not eligible due to the presence of strict pre-defined exclusion criteria (age >70 years old, uncontrolled chronic hyperthension, on-going treatment with ACE inhibitors, autoimmune disease, uncontrolled diabetes, BMI >35, ASA ≥3, patient included in other clinical trials). 4 women (10%) refused to sign informed consent. Finally, 18 patients had complete cytoreduction and received the planned treatment. Median Operative Time was 399 minutes (including 120 minutes related to HIPEC perfusion) (range 256–587) and median Estimated Blood Loss was 287.5 cc (50–600). 5 patients (29.4%) had grade 3 MSKCC early post-operative complications (3 pleural effusions requiring drainage, 2 wound dehiscence requiring VAC). Neither Acute Kidney Failure nor Grade 4–5 complications were observed. Conclusion: After adopting strict inclusion criteria, the use of HIPEC in this specific setting of patients, has an accrual rate of 82% (18/22), and a feasibility rate after surgery of 100%. The major early complication rate is 27.8%. A larger number of patients is needed to draw significant conclusions. Disclosure: Nothing to disclose.